AUTOMATED BASE OF SIMULATOR TRAINING MATERIALS FOR SPECIALITY «MAINTENANCE OF AIRCRAFT AND AIRCRAFT ENGINES» - V. A. Naida; I. A. Buyanov; P. V. Galkin (Научный вестник МГТУ ГА)
The article deals with methodical issues of development of the training materials automated base for conducting classes using a specialized simulator.